If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7p + 3 + 8p = 7 Reorder the terms: 3 + -7p + 8p = 7 Combine like terms: -7p + 8p = 1p 3 + 1p = 7 Solving 3 + 1p = 7 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 1p = 7 + -3 Combine like terms: 3 + -3 = 0 0 + 1p = 7 + -3 1p = 7 + -3 Combine like terms: 7 + -3 = 4 1p = 4 Divide each side by '1'. p = 4 Simplifying p = 4
| 9+2x=-5y | | 1.48-(-2f)=0.2 | | 2,4=t/4.5 | | 1-7/13 | | 2/100=x/68 | | -8x-6+3x=7+4x-9 | | 5u+16=101 | | -3/2x-9=-27 | | y=33x-216 | | 2x-1=6+3 | | C/8-(-12)=12 | | 0.6=-2(m+9.1) | | 21x+6+x=180 | | v=u-8 | | X/5=76 | | 1/2(8-6×)=× | | 60x+35=40x+35 | | -6x+5(x-10)=-41 | | (c+3)-2c-(1-3c)=32 | | -2u+(-3.5)=4.5 | | 0.625(x-0.33333)=0.416667 | | t^5-256t=9 | | (8-2z)/52 | | -x+3=-34 | | 35/42 | | 28-3x+3x+30-3x=40 | | X+64-42=104 | | 6.55=v/2-(-5.45) | | 15-y=273 | | 4-2x=2(x+4) | | 10x-10+10X=180 | | 4x-10+10X=180 |